Jail Versus Probation: A Gender-Specific Test of Differential Effectiveness and Moderators of Sanction Effects - Alward, Lucas M. (Criminal justice and behavior, 2018)
This study uses data from male and female adult offenders sentenced in a large urban county in the United States (n = 15,727) to examine the relative impact of jail and probation on recidivism. The study also explores how various risk and need factors moderate the effects of a jail sentence on an individual’s likelihood of rearrest. Gender-specific, multivariate logistic regression and survival analyses were conducted including risk and needs assessment data to control for individual risk for recidivism and examine risk as a moderator of sanction effectiveness. Results indicate that individuals sentenced to jail experienced an increased risk for recidivism relative to similarly situated offenders sentenced to probation. In addition, the criminogenic effect of jail was exacerbated for offenders assessed as high risk for recidivism and those with existing treatment needs. Gender-specific analyses revealed a gender-neutral criminogenic effect of jail, and gender differences in terms of moderators of sanction effects.